Gold nanoparticles supported in zirconia-ceria mesoporous thin films: A highly active reusable heterogeneous nanocatalyst - Violi, Ianina Lucila (2015)
Gold nanoparticles (NP) trapped in the mesopores of mixed zirconia-ceria thin films are prepared in a straightforward and reproducible way. The films exhibit enhanced stability and excellent catalytic activity in nitro-group reduction by borohydride and electrocatalytic activity in CO and ethanol oxidation and oxygen reduction. (Chemical Equation Presented).